Penerapan Model Pembelajaran Examples Non Examples Untuk Meningkatkan Kemampuan Menulis Puisi Siswa Kelas VIII SMP Negeri 5 Gunungsitoli - Tafonao, Sesilia Putri Kurnia Wati; Zendrato, Solina; Zalukhu, Mardian; Nazara, Silvia Niat Sari; Waruwu, Lestari (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to improve the poetry writing skills of grade VIII students of SMP Negeri 5 Gunungsitoli using the Examples Non-Examples Learning Model. This Classroom Action Research (PTK) activity is carried out in two cycles using quality and quantitative data analysis. The subjects of this study were 31 students of grade VIII-A SMP Negeri 5 Gunungsitoli. Data collection techniques using tests and non-tests consist of observation and interviews. The results of this study show that there is an increase in the ability to write poetry through the examples non examples learning model. It can be seen in the first cycle that the average score of students was 69.35 with a very good category of 19.35%, a good category of 41.94%, a sufficient category of 29.03%, and a less category of 9.68%. In the second cycle, the average score of students was 76.13 with a very good category of 38.71% and a good category of 61.29%. Based on the results of the study, the application of the Examples Non-Examples Learning Model can improve the poetry writing skills of grade VIII - A students of SMP Negeri 5 Gunungsitoli